2016
DOI: 10.3329/bjar.v41i2.28232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage duration on the stored pupae of parasitoid Bracon hebetor (Say) and its impact on parasitoid quality

Abstract: The ecto-endo larval parasitoid, Bracon hebetor (Say) is an important biocontrol agent. Effective storage methods for B. hebetor are essential for raising its success as a commercial bio-control agent against lepidopteran pests. The study was undertaken to determine the effect of storage duration on the pupae of Bracon hebetor in terms of pupal survival, adult emergence, percent parasitism, female and male longevity, female fecundity and sex ratio. Three to four days old pupae were stored for 0, 1, 2, 3, 4, 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…In our study, for middle-age P. insici pupae subjected to cold storage at 13 °C for 10 or 15 days, the number of progeny produced by post-storage adults was remarkably decreased. This is consistent with previous research on braconid parasitoids, whereby a reduction in fecundity was strongly associated with low temperature and storage period [ 28 , 33 , 36 ]. Furthermore, the reproductive parameters of P. incisi that originated from the Zhangzhou region showed a significant difference to the Hawaii P. incisi strain [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, for middle-age P. insici pupae subjected to cold storage at 13 °C for 10 or 15 days, the number of progeny produced by post-storage adults was remarkably decreased. This is consistent with previous research on braconid parasitoids, whereby a reduction in fecundity was strongly associated with low temperature and storage period [ 28 , 33 , 36 ]. Furthermore, the reproductive parameters of P. incisi that originated from the Zhangzhou region showed a significant difference to the Hawaii P. incisi strain [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with results found in D. longicaudata [ 17 ], which revealed that females that emerged from parasitized B. doralis pupae stored below 8 °C had a shorter lifespan than the control, regardless of the storage period. Likewise, the cold storage of other braconid wasps, such as Aphidius ervi (Haliday), Aphidius picipes (Nees), and Bracon hebetor (Say) (Hymenoptera: Braconidae), during the pupal stage, indicated a similar tendency in the longevity of post-storage adults [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the obvious fitness indicators such as emergence, sex ratio, longevity and fecundity, many other important fitness traits might be affected by storage and therefore impact the effectiveness of biological controls. For instance, intergenerational effects and dispersal ability are important features that should be included in post storage quality assessment (Leopold, 2007;Colinet & Hance, 2010;Alam et al, 2016). When planning cold storage of parasitoids, it is essential to determine the most appropriate storage temperatures and storage durations.…”
Section: Discussionmentioning
confidence: 99%
“…Cold storage is also advantageous while shipping parasitoids and for stockpiling parasitoids when planning future releases (Ballal et al, 1989). The effects of cold storage on the performance of parasitoids have received considerable interest (King, 1934;Hance et al, 2007;Hawes & Bale, 2007;Leopold, 2007;Colinet & Hance, 2010;Alam et al, 2016). These studies indicate that most parasitoids can be cold-stored for short periods with minimal reduction in fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Stinner 18 considered storage techniques were critical to the reduction of cost. Many studies revealed that most parasitoids can endure short-period cold storage with minimal impairment in fitness and viability 1924 . In these studies, important biological characteristics, including survival, longevity, fecundity and behavior, were evaluated 17,2529 .…”
Section: Introductionmentioning
confidence: 99%